2020
DOI: 10.1371/journal.pntd.0008227
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cholera hotspots in Zambia: A spatiotemporal analysis of cholera data from 2008 to 2017

Abstract: The global burden of cholera is increasing, with the majority (60%) of the cases occurring in sub-Saharan Africa. In Zambia, widespread cholera outbreaks have occurred since 1977, predominantly in the capital city of Lusaka. During both the 2016 and 2018 outbreaks, the Ministry of Health implemented cholera vaccination in addition to other preventative and control measures, to stop the spread and control the outbreak. Given the limitations in vaccine availability and the logistical support required for vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…We infer that these outbreaks have different origins and must have entered independently into the country from across its borders. Consistent with our observation, on a local level, case-area targeted invention strategies [ 23 , 26 , 27 ] should be employed and at the international and regional level, well-coordinated plans should be put in place to effectively control future cholera outbreaks.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We infer that these outbreaks have different origins and must have entered independently into the country from across its borders. Consistent with our observation, on a local level, case-area targeted invention strategies [ 23 , 26 , 27 ] should be employed and at the international and regional level, well-coordinated plans should be put in place to effectively control future cholera outbreaks.…”
Section: Discussionsupporting
confidence: 72%
“…When our data were analyzed at the ward level within Lusaka, the capital city and an identified cholera hotspot [ 23 ], we observed that isolates from the 2016 outbreak came from eleven wards, while the 2017/18 isolates came from three wards (Fig. 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…These differences could result from the fact that we used data for a longer time period (10 years) with rigorous statistical methods and ignored mean annual incidence ≤ 2 cases per 100 000 people while the desk review data spanned six years using mean annual incidence of 1 case per 100 000 inhabitants. As we found in this study, SaTScan has been widely used and found very helpful in identification and classification of cholera clusters (hotspots) to inform intervention measures in SSA including Cameroon [ 17 ], Uganda [ 18 ], Zambia [ 46 ], and Tanzania [ 47 ]. However, the GTFCC method is relatively new and we found no evidence of its use in published reports.…”
Section: Discussionmentioning
confidence: 99%
“…Spatiotemporal data can be analysed for building an interactive view of data points in similar and different regions, to analyse data from localized areas or to map and compare spatial distribution in individual regions [59]. In previous pandemics, spatiotemporal analysis has been used to identify cholera hotspots in Zambia [60]. With COVID-19 spreading so fast, the scientific peer-review process is struggling to catch up.…”
Section: Types Of Digital Data In Pandemic Managementmentioning
confidence: 99%